Fabricaton of poly(dimethylsiloxane) microlens for laser-induced fluorescence detection - Park, Sewan; Jeong, Yongwon; Kim, Jinseok; Choi, Kihwan; Kim, Hyeon Cheol; Chung, Doo Soo; Chun, Kukjin (JAPAN SOC APPLIED PHYSICS, 2006)
In laser-induced fluorescence (LIF) detection, the focusing of the excitation laser beam into a focal point of the. channel in a microfluidic chip is important to obtain the largest excitation intensity, and consequently to obtain the emitted fluorescence light collected to the photodetector with a high efficiency. In this paper, we present a poly (dimethylsiloxane) (PDMS) microfluidic chip consisting of an integrated PDMS microlens. The PDMS microlens was fabricated by the photoresist reflow and replica molding method. This fabrication technique is simple and has a good property in terms of the microlens and a high-dimensional accuracy. We showed that fluorescence intensities using the microlens were found to be approximately four times higher than those without the microlens. The microlens integrated on the microfluidic channel was verified to improve fluorescence intensity, and consequently signal to noise ratio.
Keywords: MICROCHIP